Missouri at Sea : Warships with Show-Me State Names - Schroeder, Richard E. (Book collections on Project MUSE., 2004)
"In Missouri at Sea, Richard Schroeder tells about the ships that were named after the state, its cities, and its favorite sons and explores the important role that each has played in American history." "For each vessel, a brief history is supplied, and the book is illustrated with many extraordinary images and photographs taken from official U.S. government records and archives. Schroeder begins his volume with the first St. Louis and other small early ships that were symbolic of America's modest nineteenth-century commercial and political ambitions. The first Missouri, one of the earliest American steamships, depicts the United States' move into the industrial and technological revolution of the nineteenth century." "The advanced technological achievements of the mid-twentieth century are represented by the nuclear submarines named for one of Missouri's favorite sons and for its capital: Daniel Boone and Jefferson City. Also highlighted in the volume is the 5,000-crew nuclear aircraft carrier Harry S. Truman, along with smaller ships named for Missouri war heroes. Missouri at Sea will appeal to those readers interested in naval history and technology or Missouri history."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.